2010
DOI: 10.1074/jbc.m109.041707
|View full text |Cite
|
Sign up to set email alerts
|

Caspase-3 Cleaves Specific 19 S Proteasome Subunits in Skeletal Muscle Stimulating Proteasome Activity

Abstract: With muscle wasting, caspase-3 activation and the ubiquitin-proteasome system act synergistically to increase the degradation of muscle proteins. Whether proteasome activity is also elevated in response to catabolic conditions is unknown. We find that caspase-3 increases proteasome activity in myotubes but not in myoblasts. This difference is related to the cleavage of specific 19 S proteasome subunits. In mouse muscle or myotubes, caspase-3 cleaves Rpt2 and Rpt6 increasing proteasome activity. In myoblasts, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
57
1
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 76 publications
(62 citation statements)
references
References 47 publications
(71 reference statements)
3
57
1
1
Order By: Relevance
“…We showed that in muscle, IL-6 in synergy with the acute phase protein, serum amyloid A, stimulates activation of caspase-3 and the ubiquitin-proteasome system to increase protein degradation in muscle. 26,27 In addition, a mechanism involving myostatin has revealed how inflammation contributes to muscle wasting. 37 In that report, pharmacologic inhibition of myostatin not only reduced the high levels of circulating inflammatory cytokines including TNF␣ and IL-6 in CKD mice it also prevented muscle wasting and improved the differentiation of MPCs.…”
Section: Discussionmentioning
confidence: 99%
“…We showed that in muscle, IL-6 in synergy with the acute phase protein, serum amyloid A, stimulates activation of caspase-3 and the ubiquitin-proteasome system to increase protein degradation in muscle. 26,27 In addition, a mechanism involving myostatin has revealed how inflammation contributes to muscle wasting. 37 In that report, pharmacologic inhibition of myostatin not only reduced the high levels of circulating inflammatory cytokines including TNF␣ and IL-6 in CKD mice it also prevented muscle wasting and improved the differentiation of MPCs.…”
Section: Discussionmentioning
confidence: 99%
“…We have also demonstrated a reduction in post-exercise caspase-3 activation following mixed protein-carbohydrate consumption, relative to carbohydrate alone (24). In addition to cleaving myofibrils, caspase-3 may also serve to stimulate proteasome activity (25), thereby both providing substrate to the UPS and increasing UPS-mediated proteolysis.…”
Section: Intramuscular Regulation Of Skeletal Muscle Proteolysismentioning
confidence: 99%
“…Moreover insulin and IGF1 inhibit the production of the 14 kDa fragment through a PI3K-dependent mechanism (PI3K, phosphoinositide-3-kinase), suggesting that these hormones have a direct effect on CASP3 in addition to their inhibition of the UPS via FoxO as described below 141 . The nature of the activation of UPS proteolysis by CASP3 in catabolic conditions has been studied further; in addition to potentially cleaving and releasing substrates for the UPS, there is evidence that in muscle tissue CASP3 cleavage of two ATPase-containing subunits on the 19S proteasome regulatory particle [PSMC1 (RPT2) and PSMC5 (RPT6)] amplifies proteasome activity 142 .…”
Section: Caspasesmentioning
confidence: 99%
“…In addition, caspase cleavage promotes atrophy by initiating myonuclear apoptosis. Caspases interact with other proteolytic systems including calpains as described above, and can also enhance proteasome activity 142 . Furthermore there is now evidence from studies in other cell types suggesting that caspase activity may have a role in actively directing a cell away from autophagy in favor of apoptosis through caspase cleavage of Beclin-1 145 .…”
Section: Caspasesmentioning
confidence: 99%